The effect of the COVID-19 pandemic on severe asthma care in Europe: will care change for good?. Issue 2 (16th May 2022) - Eger, Katrien; Paroczai, Dora; Bacon, Alison; Schleich, Florence; Sergejeva, Svetlana; Bourdin, Arnaud; Vachier, Isabelle; Zervas, Eleftherios; Katsoulis, Konstantinos; Papapetrou, Dimosthenis; Kostikas, Konstantinos; Csoma, Zsuzsanna; et al.
Background: The coronavirus disease 2019 (COVID-19) pandemic has put pressure on healthcare services, forcing the reorganisation of traditional care pathways. We investigated how physicians taking care of severe asthma patients in Europe reorganised care, and how these changes affected patient satisfaction, asthma control and future care. Methods: In this European-wide cross-sectional study, patient surveys were sent to patients with a physician-diagnosis of severe asthma, and physician surveys to severe asthma specialists between November 2020 and May 2021. Results: 1101 patients and 268 physicians from 16 European countries contributed to the study. Common physician-reported changes in severe asthma care included use of video/phone consultations (46%), reduced availability of physicians (43%) and change to home-administered biologics (38%). Change to phone/video consultations was reported in 45% of patients, of whom 79% were satisfied or very satisfied with this change. Of 709 patients on biologics, 24% experienced changes in biologic care, of whom 92% were changed to home-administered biologics and of these 62% were satisfied or very satisfied with this change. Only 2% reported worsening asthma symptoms associated with changes in biologic care. Many physicians expect continued implementation of video/phone consultations (41%) and home administration of biologics (52%). Conclusions: Change to video/phone consultations and home administration of biologics was common in severe asthma care during the COVID-19 pandemic and was associated with high satisfaction levels in most but not all cases. Many physicians expect these changes to continue in future severe asthma care, though satisfaction levels may change after the pandemic. Changes in severe asthma care caused by the #COVID19 pandemic include the transition to video/phone consultations and home administration of biologics. Patients are satisfied with the changes and show no evidence of poor asthma control. https://bit.ly/3MV6ywy